“Se eu não sei português eu não posso ir a qualquer lugar?”: ideologias linguísticas e práticas multilíngues num grupo de intercambistas - Barbosa, Izadora Araújo (2025)
This research addresses the theme of migration to Brazil, carried out by university exchange students participating in cooperation and internationalization programs with the Federal University of Goiás (UFG) as their destination. The objective is to identify how UFG exchange students reflect on their linguistic practices and how they relate these practices to their migratory experiences and decisions. Based on this use, linguistic ideologies (Blommaert, 2014) were revealed during the Linguistic Portrait workshop (Busch, 2010, 2012, 2015), which consists of recording biographical linguistic practices through the use of colors and the naming of these practices within an outline drawing of the human body. Through a reflective process, the linguistic ideologies that circulate within their experiences and migratory decisions in the university environment are brought to light. As a result, it was possible to observe how these linguistic ideologies are contradictory and are either reinforced or destabilized depending on the linguistic and social hierarchies that are intended to be maintained.